THINK-PAIR-SHARE: ENGAGING STUDENTS IN SPEAKING ACTIVITIES IN CLASSROOM - Dian Apriyanti; Mutiara Ayu (Journal of English Language Teaching and Learning, 2020)
Think-Pair-Share technique is one of the cooperative learning strategies that promote student involvement in the classroom. This strategy makes students engaged in in-class activities such as discussions and provides opportunities to share their ideas with others. The purpose of this study was to describe the implementation of the Think-Pair-Share strategy in teaching speaking skill for secondary students. A qualitative method with a descriptive analysis was undertaken in this study. The sample was twenty students of eighth grade. The data was collected through interviews, observation, and document analysis. The data analysis technique used was presented in a descriptive form. The results indicated the implementation of the Think-Pair-Share technique during the learning process took place following the stages that have been stated in the learning process plan made by the teacher. Appreciation for the implementation of the Think-Pair-Share technique both from students is quite good. Students stated that they can overcome the constraints in the learning process of speaking activity through Think-Pair-Share.